Hybanthus enneaspermus (L.) F. Muell: A concise report on its phytopharmacological aspects - Patel D.K.; Kumar R.; Sairam K.; Hemalatha S. (My University, 2025)
Hybanthus enneaspermus (L.) F. Muell belonging to the family Violaceae, popularly known as Ratanpurus (Hindi) is a herb or a shrub distributed in the tropical and subtropical regions of the world. In the Ayurvedic literature, the plant is reported to cure conditions of "Kapha" and "Pitta", urinary calculi, strangury, painful dysentery, vomiting, burning sensation, wandering of the mind, urethral discharge, blood trouble, asthma, epilepsy, cough, and to give tone to the breasts. Phytochemically, the plant contains a considerable amount of dipeptide alkaloids, aurantiamide acetate, isoarborinol, and β-sitosterol, sugars, flavonoids, steroids, triterpenes, phenols, flavones, catachins, tannins, anthraquinones and amino acids. Pharmacologically, the plant is reported to possess antidiabetic, antiplasmodial, antimicrobial, anticonvulsant, nephroprotective, aphrodisiac, hepatoprotective, antiinflammatory, aldose reductase inhibitory and free radical scavenging activities. The information provided in this review will be worthwhile to know the applicability of H. enneaspermus for the treatment of various acute or chronic diseases with a diverse nature of phytoconstituents. The overall data in this review article were collected from various scientific sources on the research of H. enneaspermus. © 2013 China Pharmaceutical University.